Extraction and Characterization of Proteins from Pachyrhizus ahipa Roots: an Unexploited Protein-Rich Crop. - Dini, Cecilia (2021)
Pachyrhizus ahipa is an unexploited crop known to be rich in proteins compared to other edible roots and tubers. These proteins are not prolamins, thus ahipa represents an interesting new source of ingredients for gluten-free foods. In this work, ahipa proteins (AP) were extracted and partially characterized in pursuit of their use as food ingredients. The effect of ultrasound treatment on protein extraction efficiency was evaluated. AP were characterized by their size, amino acid composition, surface hydrophobicity, intrinsic fluorescence, FTIR spectra, solubility, and thermal and emulsifying properties. AP were efficiently removed from the vegetal tissue using PBS or water, regardless of the use of ultrasound, but not easily recovered by precipitation. This protein fraction was composed of small proteins, with sizes ranging from 9 to 30 kDa, and highly polar. AP resulted particularly rich in aspartic acid (59% of the total amino acid content), for which they can be classified as Asp-rich proteins. Their elevated content of acidic groups was evidenced in the ATR-FTIR spectrum. The amide I band deconvolution as well as the low surface hydrophobicity and denaturation enthalpy indicated that these proteins are mainly unordered structures. The emulsifying properties of AP were enhanced when the concentration was increased from 0.1 to 1% (w/v) but resulted lower than those of soy protein. The high polarity, small size, and low isoelectric point make AP particularly suitable for acidic food matrices.